2023
DOI: 10.7759/cureus.40494
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Study on Epidemiology, Clinical Presentation, Treatment, and Outcome of Supracondylar Fractures Treated in a Base Hospital of Sri Lanka: A Single-Center Study

Fathima S Mubarak,
Muhammed A Mohamed Anzar,
Kandeepan Kanagratnam

Abstract: Introduction: Supracondylar fractures are common pediatric elbow injuries, with management in developing countries presenting challenges due to limited resources, inadequate facilities, and a lack of trained personnel. Method: This study aimed to describe the incidence, demographics, clinical presentation, treatment methods, and outcomes of supracondylar fractures treated at Ashraff Memorial Hospital (AMH)-Kalmunai, a base hospital in Sri Lanka. This is a retrospective descriptive study conducted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Supracondylar fractures can be caused by low-and high-energy mechanisms. In our study, the primary mechanism associated with fractures was a fall from standing height on the outstretched hand, which is consistent with the findings of Mubarak et al 6 and Wu et al 7 However, the exact activity being performed during the fall was not specified. For our analysis, we categorized fractures based on fall height: a short distance or standing height (<1 m) or from a greater height (>1 m).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Supracondylar fractures can be caused by low-and high-energy mechanisms. In our study, the primary mechanism associated with fractures was a fall from standing height on the outstretched hand, which is consistent with the findings of Mubarak et al 6 and Wu et al 7 However, the exact activity being performed during the fall was not specified. For our analysis, we categorized fractures based on fall height: a short distance or standing height (<1 m) or from a greater height (>1 m).…”
Section: Discussionsupporting
confidence: 91%
“…Supracondylar fractures in children can be categorized into two main types: (1) extension, in which the humerus is pushed backward at the elbow joint (accounting for 98% of cases) and can be classified using the Gartland system; and (2) flexion. Among extension fractures, type I fractures, considered simpler and conservatively treatable, are most common, representing 40-64% of cases depending on the study 1,3,4,6,14,15 . Schuller et al 3 reported an incidence of 56% for type I, 17.9% for type II, 11.1% for type III, and 14.9% for type IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are diagnosed by clinical assessment with radiological imaging, including simple radiographs or CT scans, to determine the type of fracture and assess associated injuries [ 12 ]. Conservative treatment, such as closed reduction and immobilization, is usually sufficient for minimal fractures, whereas more displaced cases may require CRPP if surgical treatment is required [ 2 , 3 ]. CRPP is a relatively standardized surgical technique for the treatment of pediatric elbow fractures and has shown favorable postoperative results [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common types of elbow fracture are supracondylar humerus fractures (SCHF), followed by lateral condylar fractures (LCF), and radial neck fractures (RNF). In children, these can be treated with closed reduction and percutaneous pinning (CRPP), if surgical treatment is indicated [ 2 , 3 ]. In pediatric elbow fractures with CRPP, intravenous opioid analgesics are commonly used for acute postoperative management of moderate to severe pain [ 4 ].…”
Section: Introductionmentioning
confidence: 99%